2022
DOI: 10.3390/jcm11175101
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Occlusion after COVID-19 Vaccination: More Coincidence than Causal Relationship? Data from a Retrospective Multicentre Study

Abstract: Background: To investigate whether vaccination against SARS-CoV-2 is associated with the onset of retinal vascular occlusive disease (RVOD). Methods: In this multicentre study, data from patients with central and branch retinal vein occlusion (CRVO and BRVO), central and branch retinal artery occlusion (CRAO and BRAO), and anterior ischaemic optic neuropathy (AION) were retrospectively collected during a 2-month index period (1 June–31 July 2021) according to a defined protocol. The relation to any previous va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Nevertheless, Feltgen et al. 15 reported that vaccination against SARS-CoV-2 was not associated with a higher risk of retinal vascular occlusive disease. Because our patient developed reduced vision 3 days after vaccination, we considered that vaccination might have been the cause of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Feltgen et al. 15 reported that vaccination against SARS-CoV-2 was not associated with a higher risk of retinal vascular occlusive disease. Because our patient developed reduced vision 3 days after vaccination, we considered that vaccination might have been the cause of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…RVO is a multifactorial vascular disease characterized by retinal blood stasis, increased venous tortuosity, intraretinal hemorrhage, and macular edema (ME), and it may cause loss of vision or blindness. 12 Branch RVO (BRVO) occurs at arteriovenous crossing regions 15 and typically occurs in middle-aged and older patients (i.e., >50 years of age) with an equal sex distribution. ME is the main cause of vision loss in patients with BRVO.…”
Section: Introductionmentioning
confidence: 99%
“…Another large retrospective study examining cerebral vascular thrombosis after both mRNA and adenoviral COVID-19 vaccination found no association between vaccination and thrombosis for either formulation of COVID-19 vaccine. An examination of more than 500 patients presenting to retina clinics with RVO found many patients had been vaccinated against COVID-19, yet no association was observed between vaccination and RVO . Retinal vascular occlusion has been described and reviewed as an established sequela of COVID-19 infection itself due to microvasculopathy and inflammation-induced hypercoagulability .…”
Section: Introductionmentioning
confidence: 99%
“…An examination of more than 500 patients presenting to retina clinics with RVO found many patients had been vaccinated against COVID-19, yet no association was observed between vaccination and RVO. 21 Retinal vascular occlusion has been described and reviewed as an established sequela of COVID-19 infection itself due to microvasc ulopathy and inflammation-induced hypercoagulability. 22,23 Epidemiologic evidence for an association between mRNA COVID-19 vaccination and RVO remains scarce due to limited sample sizes in prior studies.…”
mentioning
confidence: 99%
“…No cohort studies have investigated the relationship of COVID-19 vaccination with retinal vascular occlusion. A recent multicenter study on COVID-19 vaccination reported no evidence for retinal vascular occlusion after vaccination, via age and sex-matched case–control analysis [ 5 ]. Otherwise, studies on COVID-19 vaccination and retinal vascular occlusion were mostly limited to case reports.…”
mentioning
confidence: 99%